Silicone assisted, argon laser confinement of recurrent proliferative vitreoretinopathy related retinal detachment: a technique to allow silicone oil removal in problem eyes. Issue 9 (1st September 1997) - Steel, D H W; Weir, P; James, C R H
Abstract : AIMS/BACKGROUND: Recurrent peripheral retinal detachments may occur in eyes treated with vitrectomy and silicone oil for retinal detachments complicated by proliferative vitreoretinopathy (PVR). The aim of this study was to assess whether laser photocoagulation could be used in the presence of silicone oil to confine and stabilise recurrent PVR related peripheral retinal detachments enabling the timely removal of the oil. METHODS: 10 patients with recurrent peripheral retinal detachments after vitrectomy and silicone oil insertion were treated with posturing and subsequent focal argon laser to circumscribe the area of recurrent detachment. RESULTS: This technique alone was sufficient to limit the area of retinal detachment in seven of the cases. The remaining three cases required relieving retinotomies because of increasing retinal detachment despite the laser. In all 10 cases the silicone oil was later removed without progression of the detached areas. CONCLUSION: Silicone assisted argon laser 'confinement' can be effective in stabilising eyes with peripheral retinal detachments allowing the subsequent removal of silicone oil.